Food safety-related practices among residents aged 18-75 years during the COVID-19 pandemic: a cross-sectional study in Southwest China - Zhourong Li; Ke Jiang; Shengping Li; Tiankun Wang; Huan Zeng; Manoj Sharma; Zumin Shi; Yong Zhao (BMC, 2024)
Abstract Background Good food safety practices are essential to minimizing foodborne diseases. The present study explored the food safety-related practices of residents during the COVID-19 pandemic in Southwest China and identified the impacting factors. Methods Residents aged 18-75 years from Guizhou, Yunnan, Sichuan, and Chongqing, China, were included in our study. The convenience sampling method was used to select participants, and face-to-face surveys were conducted in households and communities to collect data. Descriptive statistics including sociodemographic characteristics of respondents and weighted percentages were obtained and the log-binomial regression was used to evaluate the influencing factors associated with food safety-related practices. Results Overall, 7,848 respondents were involved, with 97.5% efficacy. Disparities in food safety-related practices were observed between males and females, with the former performing poorer practices than the latter (70.5% vs. 68.0%, respectively). Notably, paying attention to nutrition labels when shopping for prepackaged foods was the worst practice. Age, ethnicity, region, occupation, education level, and income were identified as significant determinants of food safety-related practices. Moreover, in comparison to males, females were more likely to acquire pertinent knowledge from diverse sources, including social media, family members/ friends, books/ newspapers/ magazines, experts, and food sales staff (p < 0.05). Conclusions Males performed inferior food safety-related practices than females during the COVID-19 pandemic in Southwest China. It is suggested that future food safety education programs should incorporate diverse targeted approaches, with emphasis on males. The role of mainstream media in promoting food safety practices should be expanded and prioritized in the forthcoming initiatives.